2015
DOI: 10.1517/14656566.2015.1085509
|View full text |Cite
|
Sign up to set email alerts
|

Future of combination therapy with dabrafenib and trametinib in metastatic melanoma

Abstract: Future directions of combiDT concentrate on further combinations with immunotherapy or other targeted inhibitors, referred to triple-agent therapy, which may be essential to improving durability of responses and overcoming resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Although response rates are ∼60%, the incidence of adverse events is high and nearly all patients had at least one adverse event (98%) according to a phase II study (47). Besides, the durability of response is limited to 7-11 months due to drug resistance, which is a weakness of targeted therapy (48). By comparison, most immunotherapies do not deliver the same response rates but can offer higher durability (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although response rates are ∼60%, the incidence of adverse events is high and nearly all patients had at least one adverse event (98%) according to a phase II study (47). Besides, the durability of response is limited to 7-11 months due to drug resistance, which is a weakness of targeted therapy (48). By comparison, most immunotherapies do not deliver the same response rates but can offer higher durability (48).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the durability of response is limited to 7-11 months due to drug resistance, which is a weakness of targeted therapy (48). By comparison, most immunotherapies do not deliver the same response rates but can offer higher durability (48). Thus, combination with trametinib and immunotherapy is attractive and meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Although BRAF inhibitors, such as dabrafenib and vemurafenib, have shown a promising activity in melanoma management [ 7 ], all patients eventually develop a drug resistance at some time after treatment start [ 5 , 8 , 9 ]. The addition of a MEK inhibitor, such as trametinib or cobimetinib, to BRAF inhibitors mitigates one pathway of resistance, increasing response rates with improved overall survival (OS) without relevant cumulative toxicity [ 10 , 11 ]. In a recent exploratory analysis of survival data from selected clinical trials in metastatic melanoma with a long-term follow-up [ 12 ], mean survival curves, obtained by weighted averaging, revealed that the combination treatment with BRAF plus MEK inhibitors is clearly superior to BRAF inhibition alone in first-line treatment as well as in second line or higher line.…”
Section: Introductionmentioning
confidence: 99%
“…27,28,40,47 Clinical trial results suggest one route to treatment durability and efficacy lies in the use of combination therapies. 49,50,[64][65][66][67] Specifically, dual targeting of multiple pathways (i.e., dabrafenib + trametinib) may achieve higher patient response rates, but no durable combination therapy has yet to be determined. 49,50,[64][65][66][67] Furthermore, reported harsh side effects, such as vomiting, extreme weight loss and exhaustion, suggest a need to continue to improve therapeutic design for overall patient well-being.…”
Section: Therapeutic Challengesmentioning
confidence: 99%
“…49,50,[64][65][66][67] Specifically, dual targeting of multiple pathways (i.e., dabrafenib + trametinib) may achieve higher patient response rates, but no durable combination therapy has yet to be determined. 49,50,[64][65][66][67] Furthermore, reported harsh side effects, such as vomiting, extreme weight loss and exhaustion, suggest a need to continue to improve therapeutic design for overall patient well-being. 31-35, 40, 45, 68, 69 Collectively, these results support the continued development of novel treatments in order to improve patient response rate and treatment efficacy.…”
Section: Therapeutic Challengesmentioning
confidence: 99%